Molecular epidemiology study of a nosocomial Moraxella catarrhalis outbreak in a neurological rehabilitation unit. Issue 1 (September 2019) - Warnke, P.; Köller, T.; Kreikemeyer, B.; Barrantes, I.; Mach, H.; Podbielski, A.
Summary: Background: Moraxella catarrhalis is a common agent causing upper and lower respiratory tract infections, particularly of ventilated patients. The bacteria are transmitted between humans by direct and indirect contacts. However, reports of nosocomial outbreaks by this pathogen are scarce. Aim: To analyse M. catarrhalis strains isolated during an outbreak in a medical rehabilitation centre to reveal their clonal relationship and to elucidate potential transmission routes. Methods: Extensive environmental and medical staff sampling was performed. Phenotypic and genotypic analyses of 15 isolates were executed, including repetitive element palindromic polymerase chain reaction (repPCR) and whole-genome sequencing. Furthermore, an intensified hygiene regimen was installed. Findings: The clonal nature of nine patient isolates and a simultaneous presence of separate entities including a strain isolated from a physician during staff screening was confirmed. Although neither asymptomatic carriers among the staff persons nor outbreak strain-contaminated fomites were identified for a specific intervention, the outbreak ceased due to maximum general and specific hygiene precautions. Retrospective analysis showed the increasing prevalence of M. catarrhalis strains over a period of two years before the incidence. Since then and after returning to the regular hygiene regimen, only one patient with a phenotypically diverse M. catarrhalis isolate has been documented. Conclusion: The first M. catarrhalis outbreak involving nine patients of a neurological and trauma rehabilitation centre was reported. Potential transmission pathways were discussed. Comprehensive outbreak analyses insinuated the extension of routine laboratory storage time for defined species.